Testing Loan Loss Provisioning hypothesis for Chinese banks - Luo, Ruxin (2017)
To analyze the actual situation of Chinese banks and the realistic situation of loan loss provision, our essay tends to estimate the allocation of LLP thus increasing the profits and efficiency of banking area. Aiming to the loan loss provision of Chinese commercial banking area, this essay has collected the data of 69 banks from 2011 to 2016. There are some hypothesises like business cycle, capital management and income smoothing can be proved by the Loan Loss Provision. Therefore, it is uneasy to find trade-offs between them. The government policies and the unexpected events can sometimes mislead bank managers to make undesirable decisions (Bushman and Williams, 2012). In our essay, some determinants are defined to test the coefficients with LLP and some of them were successfully proved to be interrelated with the loan loss provisioning, including GDPG, exff, NETITA and TCETA. The results give the bank managers and banks some suggestions for the allocation of LLP in the future.